Construção de software para auxílio na decisão de condutas cirúrgicas odontológicas para pacientes com condições clínicas especiais - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Background: In the surgical training of a dental surgeon, there is a large number of patients who need additional care, leading the academic and professional to learn how to intervene in each situation, thus reducing their insecurity in care. As a form of information tool, the use of software (applications) by mobile devices, such as smartphones and tablets, has great utility and can be used in the discipline of oral surgery for teaching and consulting treatment conducts for patients who have peculiarities in their care, be it in the pre, trans and postoperative periods. The use of this tool facilitates learning and access to information. Objectives: To develop an information access tool (software/application) for dentistry academics, to identify an educational application development platform, to acquire the technical domain of this platform, to create an application for free and open operating systems (iOS/Android), easy access, and an integrative review of the literature to obtain the content that will be made available in the application. Method: the Fábrica de Aplicativos platform was adopted, which is web-accessible and allowed the creation of the application, having the following characteristics: ease of construction, without the need for knowledge of computer programming, reduced cost, free use and ease of publication in stores applications. An integrative literature review was carried out, using the PICO strategy, on the care of patients with special needs who need dental surgery, to create the content to be made available. Results: online application, available for free for information and education purposes. Conclusion: it was possible to elaborate a step by step of creating an application for educational purposes, through the online platform Fábrica de Apps, the same that was fed through an integrative literature review.
Keywords: Formação cirúrgica; Ferramenta de informação; Cirurgia odontológica; Fábrica de aplicativos; Paciente com necessidades especiais; CIÊNCIAS DA SAÚDE; Cirurgia bucal; Smartphone; Software